KEKAYAAN JENIS TUMBUHAN BERHABITUS SEMAK DI KAWASAN TAMAN HUTAN RAYA RADEN SOERJO SUB WILAYAH MOJOKERTO - Ayu Widiarti; Siti Murdiyah; Pujiastuti Pujiastuti (saintifika, 2017)
Forest is a unit of ecosystem in the form of a stretch of land containing living natural resources dominated by trees and other natural components which cannot be separated. One of Indonesian forest that has high plant species richness, is the Raden Soerjo Forest Park. The place is also rich of lower plants species due to its dimatic and environmental condition. Lower plants consist of all types of vegetation which are found under forest stands except young trees. The group of lower plant is mostly bushy. Shrubs are layer of plants that grow clumped with short stems below 1.5 meters high. This study atmed to determine the diversity of shrub in Raden Soerjo Forest Park. This type of research is descriptive exploratory research. The result showed that are 23 species of shrubs in Raden Soerjo Forest Park, those 23 are belong to 15 classis which are Asteraceae, Rubiaceae, Gesneriaceae, Elaegnaceae, Primulaceae, Fabaceae, Polygonaceae, Acanthaceae, Urticaceae, Rutaceae, Malvaceae, chloranthaceae, Verbenaceae, Solanaceae, and Rosaceae. The result of diversity of shrubs in each family is Fabaceae (low), Malvaceae (low), Asteraceae (low), Verbenaceae (low), Urticaeae (low), Solanaceae (low), Rosaceae (low), Chloranthaceae (low), Polygonaceae (low), Elaegnaceae (low), Rutaceae (low), Primulaceae (low), Acanthaceae (low), Gesneriaceae (low), dan Rubiaceae (low). The total number of plants found is 213 plants.